Potency and Diversity of Fungi on Pine Litter and Rhizosphere in Different Land-use of Universitas Brawijaya (UB) Forest - Rina Rachmawati; Akhmad Rizali; Abdul Latief Abadi; Luqman Qurata Aini; Hagus Tarno; Muhammad Febriansyah; Theresia Rani Kartika Ayu (AGRIVITA, Journal of Agricultural Science, 2022)
The agroforestry system with its diversity of vegetation has the potential on the existence of antagonistic and entomopathogen fungi. This study was conducted to evaluate the diversity of antagonistic fungi and entomopathogen fungi in the rhizosphere and pine leaf litters on pine monoculture and intercropping pine - coffee. The research was started from plot determination, sampling, fungal identification, antagonist test and pathogenicity test. The results of isolation of fungi from pine leaf litter on monoculture pine and intercropping pine-coffee fields obtained 17 genus of fungi. In monoculture pine, there 9 genus of fungi were found, while other 4 were still unidentified. In pine-coffee intercropping land 13 genus were observed. Based on the potential and bility tests, Acremonium sp. 3 and Penicillium sp. 2 has the highest inhibiton capacity, while isolate Paecilomyces sp. 1 and Paecilomyces sp. 2 had the best level of pathogenicity and mortality. Temperature and humidity did not affect the diversity of fungi. The diversity of entompathogenic and antagonistic fungi was higher in the pine-coffee intercropping land use. The litter plots had higher fungal diversity than the rhizosphere.